MÃ‰TODO PRÃTICO E ECONÃ”MICO PARA A CRIAÃ‡ÃƒO DOS PARASITOS DA ð˜‹ð˜ªð˜¢ð˜µð˜³ð˜¢ð˜¦ð˜¢ EM LABORATÃ“RIO (NOTA PRÃ‰VIA) - Gallo, Domingos (REVISTA DE AGRICULTURA, 2020)
MÃ‰TODO PRÃTICO E ECONÃ”MICO PARA A CRIAÃ‡ÃƒO DOS PARASITOS DA ð˜‹ð˜ªð˜¢ð˜µð˜³ð˜¢ð˜¦ð˜¢ EM LABORATÃ“RIO (NOTA PRÃ‰VIA)